PERANAN PENDAPATAN ASLI DAERAH (PAD) DALAM PELAKSANAAN OTONOMI DAERAH DI KOTA LHOKSEUMAWE - Syahrial, Mr; Toyo, Sutoyo (JURNAL KEBANGSAAN, 2014)
This research mainly intends to analyze the role of Regional Original Income (PAD) in the frame work territory autonomy implementation in the city of Lhokseumawe. The result is with the approach of bringing it into a relably material for arranging policy which directly points at the improvement of Regional Original Income as a realization of territory autonomy implementation. The data used in this research is the secondary data which is in the form of Regional Budget (APBD) statistical variable, comprising regional revenue (SLPATL, regional original income, tax/non-tax sharing, contribution and financial support, development revenue) and regional expenditure (regional routine exependiture outside the official exepense, routine expense of regional income service) and Regional Original Income comprising regional tax, regional retribution, Regional-owned corporation (BUMD) profit, officials revenue, and other revenues. The data is taken from financial section, and Lhokseumaweâs regional income service. The analysis method applied is descriptive statistical analysis. The analysis, during the observation period started in the fiscal year of 2001/2002 until of 2010 results in the fact that the average contribution of Regional Income resources toward its total figure, orderly arranged in succession are 53.02% of regional tax, 36.58% of regional retribution, 4.87% of other revenues, 3.53% of Regional-owned Corporation, 1.99% of officials revenue. Regional Original Income growth rate on the average is 14.76% and the highest growth rate on the average is peaked by the Regional-owned Corporation which lies whith the point of 27.15% followed by 22.19% of other revenue, 14,04 of regional tax, 13.96% of regional retribution. Fiscal Autonomy Level (DOF) as the measurement of regional capacity has a standard on the average of 32.96%. The Regional Routine Capacity Level (KRD) reaches the point of 119.15%. The administration performance of Regional Original Income collection which is measured according to effectiveness and efficiency level has figures of 102.62% of effectiveness level on the average and of 16.30% of efficiency level on the average. In the frame work of territory autonomy implementation, it is said Regional Original Income plays an important role in financing adminitration implementation and regional development. Therefore, the effort to minimalize the dependece toward central government can be realized.Keywords : Willingness to pay, coral reef, community